Sovereign stress, banking stress, and the monetary transmission mechanism in the Euro area - Oliver Holtemöller; Jan-Christopher Scherer (Halle Institute for Economic Research (IWH), 2022)
In this paper, we investigate to what extent sovereign stress and banking stress have contributed to the increase in the level and in the heterogeneity of nonfinancial firms' refinancing costs in the Euro area during the European debt crisis and how they did affect the monetary transmission mechanism. We identify the increasing effect of government bond yield spreads (sovereign stress) and the share of non-performing loans (banking stress) on firms' financing costs using an instrumental-variable approach. Moreover, we estimate both sources of stress to have significantly impaired the monetary transmission mechanism during the European debt crisis.
Keywords: E43; E44; E52; 330; banking stress; firms' financing conditions; government bond yields; interest rate channel; monetary policy transmission; sovereign stress